Effects of Aerobic Exercise on Body Composition and the Derivatives of Reactive Oxygen Metabolites & Biological Antioxidant Potential - Chang-Gyun Kim (Asian Society of Kinesiology, 2023)
OBJECTIVES This study was to investigate the effects of aerobic exercise at different intensities on body composition and the derivatives of reactive oxygen metabolites & biological antioxidant potential. METHODS The recruited subjects of thirty young men without any medical problems were divided into LEAI(light-exercise aerobic intensity, n=10), MEAI(moderate-exercise aerobic intensity, n=10), and VEAI(vigorous-exercise aerobic intensity, n=10). The variables were measured to the body compositions (%body fat, BMI & WHR) and the derivatives of reactive oxygen metabolites & biological antioxidant potential) on pre-and post-exercise protocol programs for 8 weeks. The collected blood samples from a fingertip were analyzed with FRAS evolve, H & D co., Italy. Statistical analysis used the two-way repeatedmeasures ANOVA and Tukey's test for post-hoc analysis and test of homogeneity with Levene's F value. RESULTS The results are as follows; In body compositions, %body fat was shown a significant difference between pre-and post-exercise in the VIAE group and a significant difference between LIAE & VIEA and MIEA group in post-exercise. WHR(waist to hip ratio) was shown a significant difference between LIAE & VIEA and MIEA group in post-exercise. The oxidative stress, d-ROM(derivatives of Reactive Oxygen Metabolites) was not shown a difference significantly, and BAP(Biological Antioxidant Potential) significant difference between pre-and post-exercise in LIEA & VIEA groups. CONCLUSIONS In conclusion, it increased oxidative stress parameters, the derivatives of Reactive Oxygen Metabolites, and Biological Antioxidant Potential in each group after 8 weeks of exercise. The antioxidant defense system was revealed to ensure biological safety in regular exercise situations.